ANALYSIS OF PRIMARY SCHOOL STUDENTS' WRITING ERRORS IN ENGLISH SUBJECTS - Nadilah, Siti Nadilah; Febriani Sya, Mega; Firmansyah, Willis; Hamamy, Fauziyatul (Fakultas Agama Islam dan Pendidikan Guru, 2024)
The aim of this research is to identify writing errors made by elementary school students in English subjects. The author uses qualitative research methods in the data collection or analysis process. uses literature study methods, which include books, journals and related lecture materials. The results of the evaluation display that there are mistakes that intrude with the meaning including verbs, phrase order and misspellings as well as difficult verbs. Teachers must concentrate on teaching students what is right so that they do not make the same mistakes in the future. Additionally, there are errors that may change the meaning. If college students need to realize the guidelines, however they're careless, this is considered wrong. Article errors, incorrect use of prepositions, pronoun agreements, comma splices, and minor spelling errors are among these errors